Eksklusivisme Gereja Evangelikal di Indonesia dan Semangat Kemajemukan Pancasila: Mungkinkah Keduanya Bersatu? - Tjandra, Indra Kurniadi; Deswanto, Yusuf (Veritas : Jurnal Teologi dan Pelayanan, 2023)
Pancasila is a political compromise that allows Indonesia as a nation to continue to walk together in various religious beliefs (Islam, Buddhism, Hinduism, Confucianism, Protestantism, Catholicism, and others who believe in the One God). On the other hand, the teachings and practices of the evangelical church in Indonesia, especially those related to the basic doctrine of salvation and the practice of evangelism, are often considered contrary to the values of Pancasila. This study aims to show that the fundamental beliefs of the evangelical church do not conflict with the spirit of diversity in Pancasila. Our thesis is that the basic evangelical doctrines and practices are not in conflict with the inclusivism of Pancasila, because the history of the formation of Pancasila is largely influenced by neo-modernist Muslims who were likewise exclusivist in their theology. The approach taken in this study is to explore the historical roots of the evangelical movement in the world to Indonesia, which is then compared with the history of the birth of Pancasila, to demonstrate coherence between evangelical teachings and praxis to the values of Pancasila.